(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the relationship between personality types and their patterns of social media use. The rapid growth of social networking platforms has transformed how individuals interact, express themselves, and establish relationships. Research shows that different personality traits influence not only the amount of time people spend online but also their purposes and styles of interaction. Extroverts, for example, are more likely to engage in frequent communication, seek attention, and share personal content, while introverts may use social media for information-seeking, self-expression, or controlled communication.